Implementasi Layanan Inklusi ABK pada Satuan Pendidikan pada Anak Usia Dini - Sulistyorini, Siska (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
Literature references on inclusive education emphasize more on inclusive services by involving a lot of assistance and costs. This becomes difficult when implemented in schools in developing countries with insignificant incomes and inadequate education support. Meanwhile, with the publication of this inclusive school reception, public schools will not be able to refuse registration of various children with special needs.. Therefore, with all the limitations, this literary research discusses how the minimum implementation of inclusive services that can be applied by early childhood education units. Research Results Explain that: Early implementation of inclusion services can begin by paying more attention to children with special needs in depth both indoors and outdoors. Among other things by conducting (1) identification of ABK in various ways including Assessment; (2) Taking action on the curriculum (3) Trying to meet the facilities means gradually adjusting to the needs of individual ABK students (4) giving good treatment and in accordance with the psychological basic needs of ABK students in general and trying to provide individual intervention proportionally according with special needs needed by ABK